Analysis of Junior High School Teachers’ Mathematical Literacy Skills In Solving High Order Thinking Skills (HOTS) Problems - Julianingsih, Denok; Silwana, Amalia (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
This research is a descriptive qualitative research that aims to describe the mathematical literacy skills of junior high school mathematics teachers in solving HOTS problems. Research subject selection is based on the teachers’ work period consisting of four teachers, such as two junior teachers and two senior teachers. The research instruments are HOTS problems at level 5 and level 6, and interview guidelines. The results of the research showed that in solving HOTS problem at level 5, there were junior and senior teachers who were only able to fulfill 3 of the 6 mathematical literacy indicators. In solving HOTS problem at level 6, there was junior teacher who had not fulfilled one of the mathematical literacy indicators well and there was senior teacher who could only able to fulfill just one of the mathematical literacy indicators. However, other junior and senior teachers were able to fulfill the overall mathematical literacy indicators. Hence, there are still both junior and senior teachers who have not been able to solve HOTS problems well, so they have not been able to fulfill the overall mathematical literacy indicators.